P-mTOR Expression and Implication in Breast Carcinoma: A Systematic Review and Meta-Analysis. - Xian-Fei Ding; Li-Feng Li; Xue-Liang Zhou; Li-Na Guo; Meng-Meng Dou; Yan-Yan Chi; Shao-Xuan Wu; Ya-Na Zhang; Zheng-Zheng Shan; Yi-Jie Zhang; Feng Wang; Qing-Xia Fan; et al. (PLoS ONE, 2017)
Objective Phosphorylated mammalian target of rapamycin (p-mTOR) is a promising prognostic marker in many types of cancer. However, its survival benefit in patients with breast carcinoma remains unknown. The aim of the present study was to assess the relationship between p-mTOR expression and prognosis in breast carcinoma based on a systematic review and meta-analysis. Materials and methods Electronic databases (including Pubmed, Embase, ISI web of science, and Cochrane Library) were searched up to November 24, 2015. The outcome measures were hazard ratios (HRs) with 95% confidence interval (CI) for the association between the prognosis of breast carcinoma patients and p-mTOR expression. Primary end points were disease-free survival (DFS), overall survival (OS), and recurrence-free survival (RFS). Statistical analysis was performed with STATA 12.0. Results Nine cohort studies including 3051 patients met full eligibility criteria. The pooled HRs (95% CI) for OS, DFS, and RFS were 0.84 (0.27-2.63), 0.71 (0.40-1.23), and 0.48 (0.20-1.18), respectively. Conclusions Our findings suggested that p-mTOR overexpression was not significantly related to prognosis in breast carcinoma regarding OS and disease recurrence. Prospective studies are warranted to examine the association between p-mTOR expression and survival outcomes in breast carcinoma.